2000
DOI: 10.1099/00221287-146-7-1593
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and functional conservation of σE in endospore-forming bacteria The GenBank accession numbers for the sequences determined in this work are AF225461–AF225466.

Abstract: Conservation of the sporulation processes between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The 824(pTSEG) results, especially, suggest that plasmid-borne expression of the spoIIGA-sigE-sigG operon disrupts normal sporulation, even though the spoIIGA-sigE-sigG operon was transcribed from its natural promoter and the plasmid was present at a low copy number. Previously, it was shown in B. subtilis that plasmid complementation of sigE mutants greatly reduced sporulation efficiency to 0.2% that of wild-type (WT) B. subtilis (2), and similar results were reported for plasmid complementation of a C. perfringens sigE mutant (12). Thus, even better-characterized hosts, such as B. subtilis, demonstrate a significant deviation in sporulation control when sigma factors are expressed from a replicating plasmid.…”
Section: Resultssupporting
confidence: 53%
“…The 824(pTSEG) results, especially, suggest that plasmid-borne expression of the spoIIGA-sigE-sigG operon disrupts normal sporulation, even though the spoIIGA-sigE-sigG operon was transcribed from its natural promoter and the plasmid was present at a low copy number. Previously, it was shown in B. subtilis that plasmid complementation of sigE mutants greatly reduced sporulation efficiency to 0.2% that of wild-type (WT) B. subtilis (2), and similar results were reported for plasmid complementation of a C. perfringens sigE mutant (12). Thus, even better-characterized hosts, such as B. subtilis, demonstrate a significant deviation in sporulation control when sigma factors are expressed from a replicating plasmid.…”
Section: Resultssupporting
confidence: 53%
“…The signature sequence - 5′TTTAATTCGAAGCAACGCGAAGAACCTTA3′ - shared by all the Clusters except 5 and 7 also indicates that these sequences may have a common origin similar to Lactobacillus , Paenibacillus , Clostridium , rumen bacterium, etc. [105]. Each of the clusters has certain unique signatures, which did not match with the 10 Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…It was speculated that, as with the C. acetobutylicum EKO1 and GKO1 mutants (sigE and sigG disruption mutants, respectively), plasmid-based complementation would not restore sporulation (54). In B. subtilis, plasmid complementation of a sigE mutant failed to restore WT levels of sporulation, and only by integrating the operon back onto the chromosome could WT levels of sporulation be restored (2). Although no equivalent B. subtilis study with a sigF mutant could be identified in the literature, it is possible that this is the case for sigF mutants as well.…”
Section: Disruption Of Sigfmentioning
confidence: 99%